Cravo do canavial: "entre" o maracatu rural e a mímesis corpórea: a construção de uma dramaturgia cênica - Martins, Carla Pires (2013)
The present dissertation has begun with an investigation about the application of the Technique of the Corporeal Mimesis, systematized by the Lume, Interdisciplinary Center for Theatrical Research of Unicamp, associated with the matrix of Rural Maracatu, specifically of the group Cambinda Brasileira (Nazaré da Mata PE), with the purpose of promote the training and the composition work of the actor. Starting from an empirical methodology, which used the analysis of practical experiences the application process of the Corporeal Mimesis and the construction of a theater play associated with bibliographical research, I could investigate possible ways of re-signification of this technique, using components related to the ritual and the game present in the popular event in question, and experience such paths through the conception of the play Cravo do Canavial